Plant Morphology, Paradermal Anatomy, and Leaves Metabolite Profiles of Rhododendron multicolor Miq. from Cibodas Botanic Garden, West Java, Indonesia - Devy Janisca Shalihi; Neni Murniati; Rahman, Wiguna; Hutabarat, Prima Wahyu Kusuma; Intani Quarta Lailaty (JSMARTech: Journal of Smart Bioprospecting and Technology, 2025)
Rhododendron multicolor Miq. exhibits distinctive morphoanatomical characteristics and various bioactive compounds with medicinal and horticultural potential. Numerous studies indicated Rhododendron species are widely utilized as medicinal and ornamental plants, owing to their diverse phytochemical profiles and distinctive morphoanatomical characteristics. However, comprehensive studies of the morphoanatomy and leaves metabolite profile of R. multicolor are still limited globally, as well as its minimal utilization by local communities, highlighting a significant knowledge gap. Therefore, this study aimed to analyze the morphology, paradermal anatomy, and metabolite profile of young leaves and mature leaves of R. multicolor. Morphoanatomy characteristics were analyzed descriptively, anatomical features were analyzed using specific formulas, and metabolite profiling was analyzed using qualitative phytochemicals and gas chromatography-mass spectrometry (GC-MS). The result shows that R. multicolor is a shrubby plant characterized by funnel-shaped flowers in a vibrant red hue, along with narrowly elliptic, scaly leaves. The scales are stellate lobed irregularly with lower density than stomata; the epidermis is polygonal to irregular that has a higher density compared to stomata. The results of the qualitative phytochemical test of Rhododendron multicolor are that it contains phenols, flavonoids, Mayer alkaloids, Bouchardat alkaloids, Dragendorf alkaloids, tannins, and saponins. Based on GC-MS analysis of young leaves and mature leaves of R. multicolor, a total of 31 metabolite compounds from 21 compound groups were identified, with the major compound being squalene from the terpenoid group, which has the potential to be an antioxidant, anticancer, antibacterial, antifungal, antitumor, and cardioprotective.